PENGARUH PSYCHOLOGICAL WELL-BEING DAN LONELINESS TERHADAP CELEBRITY WORSHIP PADA FANS K-POP - Wiji Lestari, Putri Wahyu; Mariyati, Lely Ika (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study analyzes the influence of psychological well-being and loneliness on celebrity worship among K-pop fans aged 18–25, categorized into three levels: entertainment-social, intense-personal, and borderline-pathological. Using a quantitative approach with a regression design and simple random sampling technique, data were collected through an online questionnaire utilizing the Celebrity Worship Scale (CWS), UCLA Loneliness Scale, and Psychological Well-Being Scale (PWBS). The results of multiple regression analysis indicate that both variables significantly influence celebrity worship, both simultaneously and partially, with a contribution of 58.7%, while the remaining 41.3% is assumed to be influenced by other factors not examined in this study, such as self-esteem, social support, or affiliation needs.